Simulation of a radiobiology facility for the Centre for the Clinical Application of Particles - Kurup,A; Pasternak,J; Taylor,R; Murgatroyd,L; Ettlinger,O; Shields,W; Nevay,L; Gruber,S; Pozimski,J; Lau,HT; Long,K; Blackmore,V; et al. (Physica Medica, 2019)
The Centre for the Clinical Application of Particles’ Laser-hybrid Accelerator for Radiobiological Applications (LhARA) facility is being studied and requires simulation of novel accelerator components (such as the Gabor lens capture system), detector simulation and simulation of the ion beam interaction with cells. The first stage of LhARA will provide protons up to 15MeV for in vitro studies. The second stage of LhARA will use a fixed-field accelerator to increase the energy of the particles to allow in vivo studies with protons and in vitro studies with heavier ions.BDSIM, a Geant4 based accelerator simulation tool, has been used to perform particle tracking simulations to verify the beam optics design done by BeamOptics and these show good agreement. Design parameters were defined based on an EPOCH simulation of the laser source and a series of mono-energetic input beams were generated from this by BDSIM. The tracking results show the large angular spread of the input beam (0.2rad) can be transported with a transmission of almost 100% whilst keeping divergence at the end station very low (<0.1mrad). The legacy of LhARA will be the demonstration of technologies that could drive a step-change in the provision of proton and light ion therapy (i.e. a laser source coupled to a Gabor lens capture and a fixed-field accelerator), and a system capable of delivering a comprehensive set of experimental data that can be used to enhance the clinical application of proton and light ion therapy.